Bobot otot dan tulang tibia itik pengging (Anas platyrhyncos domesticus L.) setelah pemberian imbuhan tepung daun kelor (Moringa oleifera Lam.) dalam pakan - Hikmah Putri Pratiwi; Kasiyati Kasiyati; Sunarno Sunarno; Muhammad Anwar Djaelani (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2019)
Moringa leaf contains the nutrient which includes carbohydrates, protein, fat, fiber, beta-N, calcium, and phosphor. Various kinds of nutrient are essential supporting the growth and productivity of Pengging ducks, both egg or meat production. The aimed of this study to analyze the effect of Moringa leaves powder in feed on the weight of tibial bone and muscle as well as the length and diameter of tibial bone in Pengging ducks. The study used a Completely Randomized Design (CRD) consisting of 5 treatments with 3 replications. The treatment included the control group (basal feed without the addition of Moringa leaves powder), the treatment of basal feed supplemented with Moringa leaves powder by 2.5; 5; 7.5; and 10%. The data wereanalyzed by one way-ANOVA and the relationship between variables can be seen from the value of the correlation coefficient. The results showed that the added Moringa leaves powder did not significantly (P > 0.05) affect the weight of the tibial bone and muscle, and the lenght and diameter of the tibial of the pengging duck. The positive correlation between the length of thetibial bone and the diameter of the tibial bone with an r-value by 0.894. It was concluded that Moringa leaves powder as feed additive of Pengging duck could not increase the weight of the tibial bone and muscle, and the length and diameter of the tibial bone had not changed.